THE IMPACT OF PICTURE SERIES ON WRITING ABILITY AMONG INDONESIAN JUNIOR HIGH SCHOOL EFL LEARNERS - Adinda Widya Ramadhanty; Dhafid Wahyu Utomo; Jalia Mayasari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study tried to shed light on investigating the impact of picture series on Indonesian Junior High School EFL learners’ abilities in English descriptive writing. To fulfill the objective, quantitative method with quasi experimental design was employed. 50 Indonesian Junior High School EFL learners were selected out of 100 students in a private Junior High School in Banten province. The sample of this research was chosen based on the non-equivalent group design technique. Moreover, the chosen participants were divided into two equal groups: experimental group and control group. In collecting the data, the researchers conducted pre-test and post-test. The data, then, were analyzed by using t-test. The result of t-test revealed that revealed that the experimental group performed better than the control group. Finally, the implications of the findings and recommendations for future research were also discussed.